Apache Tomcat 7 - Vukotic, Aleksa (The expert's voice in Java., 2011)
Apache Tomcat is the most popular open-source de-facto Java Web application server, standard for today's Web developers using JSP/Servlets. Apache Tomcat 7 covers details on installation and administration of Apache Tomcat 7. It explains key parts of the Tomcat architecture, and provides an introduction to Java Servlet and JSP APIs in the context of the Apache Tomcat server. In addition to basic concepts and administration tasks, Apache Tomcat 7 covers some of the most frequently used advanced features of Tomcat, including security, Apache web server integration, load balancing, and embedding Tomcat server in Java applications. Finally, through a practical primer, it shows how to integrate and use some of the most popular Java technologies with Apache Tomcat. In summary, Apache Tomcat 7 offers both novice and intermediate Apache Tomcat users a practical and comprehensive guide to this powerful software.